CASH DIVIDEND: Faktor-faktor yang Mempengaruhinya - Yuliani Yuliani (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2010)
The purpose of this study was to obtain empirical evidence about the influence of these factors between the Return On Investment (ROI), Cash Ratio (CaR), Current Ratio (CR), Debt to Total Asset Ratio (DTA), Earning Per Share (EPS), Cash Flow (CF) of the Cash Dividend. The population was included in LQ45 issuers.   Determination by purposive sampling. Based on the criteria selected 20 samples of the observation period from 2004 to 2008. For the purposes of analysis used panel data during the study.   While the models and methods of analysis used in this study were multiple regressions that been modified to meet the assumptions of multivariate linear models. The findings from this study: first, partially on one  equation is ROI, CaR, EPS and CF significantly influence the distribution of cash dividends. CR and DTA variable is not significant. While the simultaneous equation model can predict the one who used the cash dividend. Second, the model equations are two partial and simultaneous CFFO variables, CFFI and CFFF who use to predict the cash dividend is not significant. Key Words :   ROI, CaR, EPS, CF, CR, DTA,  CFFO, CFFI  and CFFF